FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEBIJAKAN HEDGING PERUSAHAAN DI INDONESIA - Bodroastuti, Tri; Paranita, Ekayana Sangkasari; Ratnasari, Lia (Valid Jurnal Ilmiah, 2019)
Hedging is an action taken to protect companies from exposure to exchange rates. Exposure to exchange rate fluctuations is the vulnerability of firms affected by exchange rate fluctuations. This study aims to analyze the factors that affect the company's hedging policy. The population is a nonfinancial manufacturing company listed on the Indonesia Stock Exchange (IDX) for the period of 2011-2015. The data used comes from the financial statements of each company. The analysis technique used is logistic regression analysis. The research findings show that growth opportunity negatively affect the company's hedging policy, while liquidity, firm size, financial distress, leverage, and managerial ownership have a positive effect on company's hedging policy. This finding is expected to be a consideration for investors before investing in manufacturing companies in BEI.